2011
DOI: 10.1016/j.archoralbio.2011.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus spp., Enterobacteriaceae and Pseudomonadaceae oral isolates from Brazilian HIV-positive patients. Correlation with CD4 cell counts and viral load

Abstract: The aim was to evaluate the presence of Staphylococcus spp., Enterobacteriaceae and Pseudomonadaceae in the oral cavities of HIV-positive patients. Forty-five individuals diagnosed as HIV-positive by ELISA and Western-blot, and under anti-retroviral therapy for at least 1 year, were included in the study. The control group constituted 45 systemically healthy individuals matched to the HIV patients to gender, age and oral conditions. Oral rinses were collected and isolates were identified by API system. Counts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
3
19
0
2
Order By: Relevance
“…Likewise, respiratory pathogens were detected in supragingival plaque of 85.3% hospitalized chronic lung-diseased patients compared to 38.7% of lunghealthy dental outpatients [21]. In HIV-infected patients, several studies have also indicated high frequencies and levels of enterobacteria, pseudomonas, Acinetobacter baumannii, C. albicans, and E. faecalis in the subgingival microbiota associated to necrotizing periodontitis, chronic periodontitis or periodontal health [39][40][41][42]. Regarding systemically healthy individuals presenting periodontal diseases, our current findings showed that approximately 42% of the tested species (C. albicans, enterobacteria, H. alvei, Neisseria spp., O. uli and S. marcescens) were detected in significantly higher prevalence and counts in diseased than periodontally healthy patients.…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, respiratory pathogens were detected in supragingival plaque of 85.3% hospitalized chronic lung-diseased patients compared to 38.7% of lunghealthy dental outpatients [21]. In HIV-infected patients, several studies have also indicated high frequencies and levels of enterobacteria, pseudomonas, Acinetobacter baumannii, C. albicans, and E. faecalis in the subgingival microbiota associated to necrotizing periodontitis, chronic periodontitis or periodontal health [39][40][41][42]. Regarding systemically healthy individuals presenting periodontal diseases, our current findings showed that approximately 42% of the tested species (C. albicans, enterobacteria, H. alvei, Neisseria spp., O. uli and S. marcescens) were detected in significantly higher prevalence and counts in diseased than periodontally healthy patients.…”
Section: Discussionmentioning
confidence: 93%
“…Enterobacteria and Pseudomonas ssp were more commonly found in patients with low T CD4 counts (p=0.011), but there was no statistically significant difference concerning the viral load. (12) In Los Angeles, a study that assessed 4,825 patients with HIV observed a strong correlation be- tween low T CD4 counts and the presence of Pseudomonas aeruginosa. (16) The viral load count in most of the patients with positive samples for gram-negative bacteria was above 100,000 copies/ml.…”
Section: Discussionmentioning
confidence: 99%
“…in the oral cavity of patients with both positive and negative HIV showed a higher growth of gram-negatives in the group of positive HIV patients (p=0.001); additionally, there was no statistically significant difference between the groups regarding the Staphylococcus spp. (12) A research carried out in Thailand assessed positive blood cultures of 140 patients with HIV undergoing antiretroviral therapy. The study found that most of the patients were men (65%), with a mean age of 38 years, and showed a predominance of gram-negatives (40%).…”
Section: Discussionmentioning
confidence: 99%
“…Aas et al reported that Streptococcus species were more commonly detected in supragingival plaque of HIV-infected individuals with low viral loads, compared with non-HIVinfected control individuals (Aas et al, 2007). A recent study by Back-Brito and HIV Infection Affects Streptococcus mutans Levels, but not Genotypes co-workers reported that HIV infection could affect salivary microbial diversity (Back-Brito et al, 2011). Madigan and colleagues found that levels of mutans streptococci and Lactobacillus, as cariogenic oral flora indicators, were correlated with HIV status in HIV-infected children (Madigan et al, 1996).…”
Section: Introductionmentioning
confidence: 99%